2005
DOI: 10.1111/j.1440-1746.2005.03776.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gastroesophageal reflux disease using a new questionnaire

Abstract: A novel questionnaire was developed. It was designed to detect the symptoms of GERD while simultaneously excluding non-GERD patients. This simplified nine-item simplified questionnaire had a sensitivity of 79.8%, a specificity of 53.6% and an accuracy of 63.4%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 11 publications
(9 reference statements)
2
22
0
Order By: Relevance
“…Shimoyama et al reported less prevalence of pain in stomach at night in GERD group (grade M or worse) as one of differences between GERD group and non-GERD group (ulcer, gastritis etc.) [30]. As a result, when combining the results of these studies and the present study, acid reflux appears to be mild in grade N, and in terms of symptoms, grade N resembles EPS-type FD associated with ulcer symptoms (stomachache).…”
Section: Discussionsupporting
confidence: 46%
“…Shimoyama et al reported less prevalence of pain in stomach at night in GERD group (grade M or worse) as one of differences between GERD group and non-GERD group (ulcer, gastritis etc.) [30]. As a result, when combining the results of these studies and the present study, acid reflux appears to be mild in grade N, and in terms of symptoms, grade N resembles EPS-type FD associated with ulcer symptoms (stomachache).…”
Section: Discussionsupporting
confidence: 46%
“…Over use of upper endoscopy contributes to higher health care costs without improving patient outcomes, so for identification of GERD symptoms in every day clinical practice, the questionnaire are developed and used as FSSG [12] . The questions related to 12 symptoms that the patients with GERD complain of most not only heart burn and acid taste but also dyspeptic symptoms such as heavy stomach and feeling full quickly [16] . In our study, there is significant frequency of heartburn, regurgitation and epigastric pain or discomfort in male than female and older age than younger age and this in agreement of the findings of El-Serag and Sonnenberg (1997) [17] .…”
Section: Resultsmentioning
confidence: 99%
“…When the cutoff was set at 8 points, FSSG showed a sensitivity of 62% and a specificity of 59% [72,73]. Table 2 presents a summary of the prevalence of symptomatic GERD in Japan [30,43,45,[54][55][56][57][74][75][76][77][78][79][80][81].…”
Section: Prevalence and Clinical Characteristics Of Symptomatic Gerd mentioning
confidence: 99%